DEVELOPMENT OF E-STUDENTWORKSHEET BASED ON SCIENCE LITERACY (E-SWBSL) OF ACID BASE TOPIC TO IMPROVE STUDENT LEARNING OUTCOME - Putra, M. Rizki Fadhli; Mitarlis, Mitarlis (Universitas Negeri Surabaya, 2023)
This study aims to develop (E-SWBSL) electronic student worksheets based on scientific literacy to improve student learning outcomes on acid-base materials that are appropriate for use. The principle of scientific literacy in the E-SWBSL includes several domains: the content knowledge domain, context domain, scientific phenomena domain, and attitude domain. The research method used a 4-D development model (Define, Design, Develop, and Disseminate), but the research only reached the development stage. The results of the E-SWBSL were tested on 22 students in the eleventh grade of pharmacy vocational school. The feasibility of E-SWBSL is viewed from three aspects, namely aspects of validity, practicality, and effectiveness. The results of the development of E-SWBSL found that the eligibility of the E-SWBSL was assessed from its validity was stated to be very valid with a validity percentage of 81.25%. The practicality of this E-SWBSL shows practical results with the value shown by the positive response questionnaire results of students with a percentage of 78.7%. The effectiveness of the E-SWBSL states very effective results based on a significant increase in student learning outcomes through the paired sample t-test, so that the developed E-SWBSL is declared feasible for use in the teaching and learning process, especially acid-base topics.